The Role of Islamic Scholars in the Education of Muslim Youth Against Violent Extremism - Rasul A. Gulo (RIRAI Publisher, 2022)
This study targets to explain the roots of violent extremism in Philippines particularly in Mindanao wherein various terrorist attacks were being conducted. The researcher also looks on education interventions that have been implemented in fragile communities and/or those that have targeted high risk groups, as a way of discouraging violent extremism. The study employed the descriptive – evaluative method of research, with the researcher made survey questionnaire as the principal instrument for data gathering. The setting of the study is the City of Cotabato which is composed of various Islamic schools and institutions that offers Religion and Theology courses. Cotabato City is formerly part and the regional center of Region XII. But due to the ratification of the Bangsamoro Organic Law, it is now part of BARMM and served as the regional center. Being an independent component city, it's not a subject to regulation from the Provincial Government of Maguindanao where it is geographically located. The respondents of this study were the Islamic teachers (Mudarrisun) of selected Islamic schools (Madaris) and Professors (Asatidz) of Islamic Studies in selected institutions in Cotabato City that offer Religion and Theology courses. Only fifty (50) respondents were finally chosen to constitute the sample of the study which is complete enumeration of the target sample population. As a descriptive – evaluative study, the data were analyzed using descriptive statistical tools, mean, standard deviation, frequency distribution and percentage. Frequency distribution was used to facilitate computation of summary values, such as the mean and standard deviation. Percentage was used to describe and compare relative proportion of categories. The mean and standard deviation were used to describe the typical perception and the variability of the perceptions of the respondents, respectively.